Discrete choice experiments in the analysis of consumers' preferences for finfish products: A systematic literature review. (September 2020) - Cantillo, Javier; Martín, Juan Carlos; Román, Concepción
Highlights: Papers that analyse preferences for finfish products using DCEs were reviewed. We summarize the main insights of consumer behaviour towards finfish products. The most used attributes for this type of experiments were identified. Willingness to pay estimations from these publications were compared and discussed. Abstract: Discrete choice experiments (DCEs) have become an important tool for assessing the preferences of consumers for finfish seafood products. This investigation presents a systematic literature review of studies performed in the last 20 years (2000–2019) that use DCEs to analyse consumers' preferences for finfish products, with the purpose to identify the main insights of consumer behaviour towards these products, the most used attributes for this type of experiments and to discuss and compare some willingness to pay estimations. We found that origin was the most used attribute for this kind of experiments, while other important factors were the harvest method, a specific certification label and the species or products considered. The WTP estimates evidenced that consumers are willing to pay premiums for domestic products, while similarly, wild products were preferred over farmed products. Also, there were higher WTP estimates for certified products, in which specific certification labels were better options rather than just claiming that the product was certified or not. All claims and labels related to sustainability, nutritional, health and safety information provided premiums that consumers were willing to pay, however, the importance differed depending on the type of label or claim, the country and species. Future research should consider the influence of being or not the main purchaser in the household, as it might affect the WTP values. Also, given the importance, future research extensions using DCEs are needed on the Chinese and Asian finfish market.